INTEGRATED MULTIVARIATE ANALYSIS TO EVALUATE EFFECTS OF PRESLAUGHTER HANDLING ON PORK QUALITY - Machado, Sivanilza T.; Santos, Rodrigo C.; Caldara, Fabiana R.; Goncalves, Manoel C.; Naeaes, Irenilza de A. [UNESP] (Soc Brasil Engenharia Agricola, 2014)
The aim of this study was to investigate the effect of pre-slaughter handling on the occurrence of PSE (Pale, Soft, and Exudative) meat in swine slaughtered at a commercial slaughterhouse located in the metropolitan region of Dourados, Mato Grosso do Sul, Brazil. Based on the database (n = 1,832 carcasses), it was possible to apply the integrated multivariate analysis for the purpose of identifying, among the selected variables, those of greatest relevance to this study. Results of the Principal Component Analysis showed that the first five components explained 89.28% of total variance. In the Factor Analysis, the first factor represented the thermal stress and fatiguing conditions for swine during pre-slaughter handling. In general, this study indicated the importance of the pre-slaughter handling stages, evidencing those of greatest stress and threat to animal welfare and pork quality, which are transport time, resting period, lairage time before unloading, unloading time, and ambience.
Keywords: transport operation; ambience; PSE meat; multivariate analysis